Au/TS‐1 catalyst for propene epoxidation with H2/O2: A novel strategy to enhance stability by tuning charging sequence. Issue 11 (29th May 2016) - Feng, Xiang; Liu, Yibin; Li, Yichuan; Yang, Chaohe; Zhang, Zhihua; Duan, Xuezhi; Zhou, Xinggui; Chen, De
Abstract : For propene epoxidation with H2 and O2, the catalytic performance of Au/TS‐1 catalyst is extremely sensitive to preparation parameters of deposition‐precipitation (DP) method. In this work, effect of charging sequence in DP process on catalyst structure and catalytic performance of Au/TS‐1 catalyst is first investigated. For different charging sequences, the compositions of Au complexes (e.g., [AuCl(OH)3 ] − ) and pore property of TS‐1 (i.e., with or without H2 O prefilling micropores) could affect the transfer of Au complexes into the micropores, resulting in different Au locations and thus significantly different catalytic performance. Notably, when TS‐1 is first filled with H2 O and then mixed with Au complexes, the reduced Au/TS‐1 catalyst could expose Au nanoparticles on the external surface of TS‐1 and show high stability. The results provide direct evidence showing that micropore blocking is the deactivation mechanism. Based on the results, a simple strategy to design highly stable Au/Ti‐based catalysts is developed. © 2016 American Institute of Chemical Engineers AIChE J, 62: 3963–3972, 2016